Predicting elite success: Evidence comparing the career pathways of top 10 to 300 professional tennis players. Issue 5 (December 2020) - Li, Pingwei; Weissensteiner, Juanita R; Pion, Johan; Bosscher, Veerle De
The aim of this research was to explore at what age professional tennis players at different ranking levels (top 10, 11-20, 21–50, 51–100, 101–200, 201–300) started playing tennis and had achieved their career ranking milestones, and to explore the viability of using age and ranking to predict a player's future success. 373 top 300 ranked professional tennis players from 2010 to 2018, including 193 females (M = 32.3, SD = 3.5) and 180 males (M = 34.0, SD = 3.1) were examined. Descriptive methods and univariate analyses were used to compare player developmental trajectories by player peak ranking levels. Discriminant analyses were applied to explore to what extent age and early ranking milestones can be used to predict a player's future peak rankings. Results revealed that there were no significant differences regarding the age at which players started playing tennis by players' career peak ranking levels. Results showed that 75% of the top 300 players started playing tennis between the ages of 3 to 7 years, whilst 21% started between 7 to 10 years, and 4% started later between 10 to 13 years. Results further showed that professional rankings between 14 and 18 years were not reliable in predicting a player's future ranking. Closer analyses revealed that age and early rankings have a relatively high value in "predicting" the ranking of higher-ranked (e.g., top 10) and lower-ranked (e.g., top 201–300) players, but not middle-ranked players (i.e. top 11–200), with nearly 60% of them not correctly classified and the top 51–100 ranked players having the lowest predictability.